(untitled) (Olhar de Professor, 2011)
This text reflects on the role of the teacher / researcher in the collective construction of Political-Pedagogical Project, understood as an instrument that organizes and consolidates pedagogical work (teaching, research, and outreach projects) at universities. Based on the assumption that the Political-Pedagogical Project establishes the principles, guidelines and purposes of the pedagogical action, the study tried to point out the references and elements that support the collective construction of the project at universities. To this end, the teacher / researcher is challenged to break down certain barriers that university tradition has built up, and to take a stance that will make a difference in the everyday life of the institution.